Quality Assurance in Higher Education
XII, 264 p.
Keywords: By bringing together leading experts on quality assurance in higher education from seven countries (from Europe, the USA and South Africa), this volume intends to go several steps further than most publications on quality assurance. First, it brings together views from micro to macro levels in the multi-actor space, showing how quality assurance impacts the higher education system throughout. Second, it links quality assurance solidly to issues of regulation, translation (rather than mechanical ‘implementation’) and transformation, instead of being only focused on quality assurance as a single policy instrument. Third, it uses this broad range of research insights to criticize current practices, explaining for instance why sometimes people have difficulty in tracing any concrete effects of all initiatives taken in this area. Finally, the book offers proposals for better focusing quality assurance in the future to address institutional challenges better. The general purpose of the book then is to give an engaged, academic reflection on how quality assurance is embedded in higher education and in a dynamic way to assess its impacts and potential improvements.